Problem-based learning in the physical science classroom, K-12 - McConnell, Tom J., 1962-; Parker, Joyce, 1955-; Eberhardt, Janet, 1952- (National Science Teachers Association, 2018)
"This book presents a discussion of the PBL structure and its application for the K-12 physical science classroom. It also includes a collection of PBL problems developed as part of the Problem-Based Learning Project for Teachers, a National Science Foundation-funded professional development program that used the PBL framework to help teachers develop a deeper understanding of science concepts in eight different content strands. The problems presented in this book were developed by content experts who facilitated the workshops and revised the problems over the course of four iterations of the workshops"--